2015
DOI: 10.1371/journal.pone.0120642
|View full text |Cite
|
Sign up to set email alerts
|

Ascites Bacterial Burden and Immune Cell Profile Are Associated with Poor Clinical Outcomes in the Absence of Overt Infection

Abstract: Bacterial infections, most commonly spontaneous bacterial peritonitis in patients with ascites, occur in one third of admitted patients with cirrhosis, and account for a 4-fold increase in mortality. Bacteria are isolated from less than 40% of ascites infections by culture, necessitating empirical antibiotic treatment, but culture-independent studies suggest bacteria are commonly present, even in the absence of overt infection. Widespread detection of low levels of bacteria in ascites, in the absence of perito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 38 publications
4
43
0
1
Order By: Relevance
“…The marker expression of PosC-SBP, with low levels of HLA-DR, CD11b, CD16, and CD86, suggests an impaired ability for antigen presentation, phagocytosis, and adhesion [29]. A similar low HLA-DR expression has recently been described on ascitic macrophages from patients with NegC-SBP, and it has been associated with a high bacterial DNA burden [9].…”
Section: Phenotypic Profile Of Ascitic Macrophagesmentioning
confidence: 60%
“…The marker expression of PosC-SBP, with low levels of HLA-DR, CD11b, CD16, and CD86, suggests an impaired ability for antigen presentation, phagocytosis, and adhesion [29]. A similar low HLA-DR expression has recently been described on ascitic macrophages from patients with NegC-SBP, and it has been associated with a high bacterial DNA burden [9].…”
Section: Phenotypic Profile Of Ascitic Macrophagesmentioning
confidence: 60%
“…We previously reported that, even in the absence of overt infection and despite SBP prophylaxis, ascites bacterial DNA levels were associated with poor clinical outcomes (death, hospital readmission) (7). Bacterial DNA levels were also associated with reduced HLA-DR expression on ascites macrophages/monocytes (CD14 + cells), suggesting a reduced antigen presentation capacity (7), which may contribute to susceptibility to infection in these patients (8). The presence of macrophages in general, however, correlated with reduced ascites neutrophils and bacterial DNA, suggesting that restoring macrophage function (e.g., HLA-DR expression; ref.…”
Section: Introductionmentioning
confidence: 99%
“…MiR-125b and miR-155 are both involved in macrophage activation1015, which are next to lymphocytes the predominant cell population in ascites16. In murine peritoneal macrophages, miR-125b was upregulated after induction of peritonitis and re-stimulation with lipopolysaccharide (LPS); it was identified as a potential mediator of tolerance to LPS17.…”
mentioning
confidence: 99%